2011
DOI: 10.1111/j.1741-1130.2011.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Families With Parents With Intellectual Disability: Views and Experiences of Professionals in the Field

Abstract: Professionals and parents with intellectual disability often disagree on what support is needed and how it should be provided. Parents report having little say in the matter, feeling coerced into accepting services that they do not find useful. Professionals may describe the parents as difficult to engage and not open to receiving help. The aim of this article was to capture the views and experiences of professionals working with parents with intellectual disabilities. A qualitative analysis of focus group dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 18 publications
0
23
0
5
Order By: Relevance
“…In an Australian study (Llewellyn et al, 2003) of care proceedings, 9% of the children had parents with IDs and thus this parent group is substantially overrepresented in care proceedings. Starke (2011) reported that views and experiences among professionals, working with parents with IDs, differed according to whether the child was living with the parent or the child had been placed in out-of-home care. When the child was living at home, the professionals were worried about the parental skills and the parents' inability to fulfill the needs of the child.…”
Section: Discussionmentioning
confidence: 97%
“…In an Australian study (Llewellyn et al, 2003) of care proceedings, 9% of the children had parents with IDs and thus this parent group is substantially overrepresented in care proceedings. Starke (2011) reported that views and experiences among professionals, working with parents with IDs, differed according to whether the child was living with the parent or the child had been placed in out-of-home care. When the child was living at home, the professionals were worried about the parental skills and the parents' inability to fulfill the needs of the child.…”
Section: Discussionmentioning
confidence: 97%
“…Cette croyance, qui peut s'expliquer par le manque de connaissances et de compréhension à l'égard de la DI et de ses conséquences sur la vie d'une personne (Booth, McConnell et Booth, 2006;Cleaver et Nicholson, 2007;McBrien et Power, 2002), peut se traduire par des présomptions erronées, des attentes inadaptées et des attitudes négatives à l'égard des parents ayant une DI/LI (McConnell et al, 1997), autant d'attitudes qui ont des retombées négatives sur l'efficacité de la relation d'aide et sur le succès du projet parental (Aunos et Feldman, 2002).Outre ces croyances, d'autres éléments constituent des obstacles à une intervention professionnelle adéquate avec ces personnes. La perception d'un manque de volonté à coopérer est l'un d'entre eux (Starke, 2011). Or, cette « apparence » de manque de volonté peut être expliquée par diverses raisons.…”
Section: Facteurs Relatifs Aux Interactions Parentsintervenantsunclassified
“…Studies have shown positive experiences of mothers with intellectual disabilities, including their considerable focus on their children's needs treated as central to self-assessment of their motherhood. Mothers with intellectual disabilities are happy, pleased and satisfied with their role, but at the same time they are able to reflect on its quality and significance of the supporting individuals [22][23][24]. Fulfilling the role of a mother strengthens the status of an adult and allows to reduce negative social implications of the "mentally disabled" label [Edmonds,in 25].…”
Section: Introductionmentioning
confidence: 99%
“…They mention the feeling of loneliness in acting as a parent, its source being their own disability [25]. Women with intellectual disabilities realize that their parental competences are subject to criticism, especially by members of their families [22,24,25,27,28].…”
Section: Introductionmentioning
confidence: 99%